Functional recovery in T13-L1 hemisected rats resulting from peripheral nerve rerouting: role of central neuroplasticity - (:unkn) unknown (FUTURE MEDICINE LTD, 2008)
Background: Functional improvements after spinal cord injury (SCI) have been reported anecdotally following neurotization, in other words, rerouting nerves proximal to injured cord segments to distal neuromuscular targets, although the underlying mechanisms remain largely unknown. Aim: To test our hypothesis that neurotization-mediated recovery is primarily attributable to CNS neuroplasticity that therefore manifests optimal response during particular therapeutic windows, we anastomosed the T12 intercostal nerve to the ipsilateral L3 nerve root 1-4 weeks after T13-L1 midline hemisection in rats. Results: While axonal tracing and electromyography revealed limited reinnervation in the target muscles, neurobehavioral function, as assessed by locomotion, extensor postural thrust and sciatic functional index of SCI rats receiving neurotization 7-10 days postinjury (n = 11), recovered to levels close to non-SCI controls with neurcitization only (n = 3), beginning 3-5 weeks postanastomosis. Conversely, hindlimb deficits were unchanged in hemisected controls with sham neurcitization (n = 7) or 4 weeks-delayed neurcitization (n = 3) and in rats that had undergone T13-L1 transection plus bilateral anastomoses (n = 6). Conclusion: Neurotized SCI animals demonstrated multiparameters of neural reorganization in the distal lumbar cord, including enhanced proliferation of endogenous neural stem cells, increased immunoreactivity of serotonin and synaptophysin, and neurite growth/sprouting, suggesting that anastomosing functional nerves with the nerve stump emerging distal to the hemisection stimulates neuroplasticity in the dysfunctional spinal cord. Our conclusion is validated by the fact that severance of the T13-L1 contralateral cord abolished the postanastomosis functional recovery. Neurotization and its neuroplastic sequelae need to be explored further to optimize clinical strategies of post-SCI functional repair.
Keywords: anastomosis; hemisection; neural stem cell; peripheral nervous system; regeneration; rehabilitation; spinal cord injury; synaptophysin; SPINAL-CORD-INJURY; FIBROBLAST-GROWTH-FACTOR; NEURAL STEM-CELLS; NITRIC-OXIDE; ADULT-RAT; ELECTRICAL-STIMULATION; CONTUSION INJURIES; PHYSICAL-ACTIVITY; PRECURSOR CELLS; MOTOR FUNCTION